Disentangling synergistic disease dynamics: Implications for the viral biocontrol of rabbits. (9th July 2018) - Wells, Konstans; Fordham, Damien A.; Brook, Barry W.; Cassey, Phillip; Cox, Tarnya; O'Hara, Robert B.; Schwensow, Nina I.
Abstract: European rabbits ( Oryctolagus cuniculus ) have been exposed to rabbit haemorrhagic disease virus (RHDV) and myxoma virus (MYXV) in their native and invasive ranges for decades. Yet, the long‐term effects of these viruses on rabbit population dynamics remain poorly understood. In this context, we analysed 17 years of detailed capture–mark–recapture data (2000–2016) from Turretfield, South Australia, using a probabilistic state‐space hierarchical modelling framework to estimate rabbit survival and epidemiological dynamics. While RHDV infection and disease‐induced death were most prominent during annual epidemics in winter and spring, we found evidence for continuous infection of susceptible individuals with RHDV throughout the year. RHDV‐susceptible rabbits had, on average, 25% lower monthly survival rates compared to immune individuals, while the average monthly force of infection in winter and spring was 38%. These combined to result in an average infection‐induced mortality rate of 69% in winter and spring. Individuals susceptible to MYXV and immune to RHDV had similar survival probabilities to those having survived infections from both viruses, whereas individuals susceptible to both RHDV and MYXV had higher survival probabilities than those susceptible to RHDV and immune to MYXV. This suggests that MYXV may reduce the future survival rates of individuals that endure initial MYXV infection. There was no evidence for long‐term changes in disease‐induced mortality and infection rates for either RHDV or MYXV. We conclude that continuous, year‐round virus perpetuation (and perhaps heterogeneity in modes of transmission and infectious doses during and after epidemics) acts to reduce the efficiency of RHDV and MYXV as biocontrol agents of rabbits in their invasive range. However, if virulence can be maintained as relatively constant through time, RHDV and MYXV will likely continue realizing strong benefits as biocontrol agents. Abstract : Synergistic disease dynamics of viruses used as biocontrol agents against invasive rabbits uncovered: Myxoma virus reduces future survival of rabbits that endure infection and become less resistant to rabbit haemorrhagic disease virus. Both viruses continue to efficiently reduce rabbit populations despite long‐term coexistence.